2004
DOI: 10.1016/j.immuni.2004.08.014
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Division and Death Are Segregated by Mutation of TCRβ Chain Constant Domains

Abstract: We have studied the role of the T cell receptor (TCR) beta chain transmembrane and cytoplasmic domains (betaTM/Cyto) in T cell signaling. Upon antigen stimulation, T lymphocytes expressing a TCR with mutant and betaTM and Cyto domains accumulate in large numbers and are specifically defective in undergoing activation-induced cell death (AICD). The mutant TCR poorly recruits the protein adaptor Carma-1 and is subsequently impaired in activating NF-kappaB. This signaling defect leads to a reduced expression of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…Furthermore, full-length p73a is the major isoform induced by TCR signaling and is required for apoptosis of activated T cells [25,28,36]. Thus, we proceeded to investigate the induction of p73 in activated SAP -/-OT-I cells, in order to elucidate the cause of reduced cell death in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, full-length p73a is the major isoform induced by TCR signaling and is required for apoptosis of activated T cells [25,28,36]. Thus, we proceeded to investigate the induction of p73 in activated SAP -/-OT-I cells, in order to elucidate the cause of reduced cell death in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Two transcription factors, E2F-1 and p73, are indispensable for the induction of AICD of T cells through this pathway, since primary T cells lacking either of these proteins are resistant to TCR-mediated apoptosis [25][26][27]. In addition, decreased levels of E2F-1 and p73 expression have been shown to be responsible for defective AICD in T cells carrying a mutation in the transmembrane region of the TCR b chain [28]. Within this pathway, Bcl-2 and Bcl-xL have anti-apoptotic function through the stabilization of the mitochondrial membrane potential.…”
Section: Introductionmentioning
confidence: 99%
“…An implication of this finding was that proliferating T cells frequently die during proliferation unless TLR agonists are present to prevent cell loss. Although several studies have measured T cell death during division in culture models of clonal expansion [13][14][15] it is not possible to do similar studies in intact animals due to rapid phagocytosis of dead or dying T cells [16]. Even in the thymus, in which approximately 98% of developing T cells are destined to die, it is only possible to detect apoptotic remnants of cells with great difficulty [17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been reported that a mutant of the transmembrane and cytoplasmic domains of the TCRb chain is impaired in recruiting Carma1 and Bcl10 and consequently in activating NF-kB. 67 In addition to being important for the recruitment of Bcl10 to the IS, Carma1 may also be important for the recruitment of PKCy. 66 However, another study did not reach the same conclusion but rather concluded that recruitment of PKCy to central and peripheral IS occurred normally in Carma1 deficient T cells.…”
mentioning
confidence: 99%